Cross-hedging of correlated exchange rates - Udo Broll; Kit Pong Wong (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2011)
This paper examines the behavior of a competitive exporting firm that exports to two foreign countries under multiple sources of exchange rate uncertainty. The firm has to cross-hedge its exchange rate risk exposure because there is only a forward market between the domestic currency and one foreign country's currency. When the firm optimally exports to both foreign countries, we show that the firm's production decision is independent of the firm's risk attitude and of the underlying exchange rate uncertainty. We show further that the firm's optimal forward position is an over-hedge or an under-hedge, depending on whether the two random exchange rates are positively or negatively correlated in the sense of expectation dependence.
Keywords: D21; D24; D81; F31; 330; correlated exchange rates; cross-hedging; exports; production